Disrupted Circadian Rest-Activity Cycles in Inflammatory Bowel Disease Are Associated With Aggressive Disease Phenotype, Subclinical Inflammation, and Dysbiosis - Swanson, Garth R.; Kochman, Nicole; Amin, Jaimin; Chouhan, Vijit; Yim, Wesley; Engen, Phillip A.; Shaikh, Maliha; Naqib, Ankur; Tran, Laura; Voigt, Robin M.; Forsyth, Christopher B.; Green, Stefan J.; et al. (Frontiers in Medicine, 2022)
Background: Patient with inflammatory bowel disease (IBD) – Crohn’s disease (CD) and ulcerative colitis (UC), have poor sleep quality. Sleep and multiple immunologic and gastrointestinal processes in the body are orchestrated by the circadian clock, and we recently reported that a later category or chronotype of the circadian clock was associated with worse IBD specific outcomes. The goal of this study was to determine if circadian misalignment by rest-activity cycles is associated with markers of aggressive disease, subclinical inflammation, and dysbiosis in IBD. Methods: A total 42 patients with inactive but biopsy-proven CD or UC and 10 healthy controls participated in this prospective cohort study. Subjects were defined as having an aggressive IBD disease history [steroid dependence, use of biologic or immunomodulator, and/or surgery] or non-aggressive history. All participants did two weeks of wrist actigraphy followed by measurement of intestinal permeability and stool microbiota. Wrist actigraphy and was used to calculate circadian markers of rest-activity– interdaily stability (IS), intradaily variability (IV), and relative amplitude (RA). Results: Aggressive IBD history was associated with decrease rest-activity stability (IS) and increased fragmentation compared to non-aggressive IBD and health controls at 0.39 ± 0.15 vs 0.51 ± 0.10 vs vs 0.55 ± 0.09 (P < 0.05) and 0.83 ± 0.20 vs 0.72 ± 0.14 (P < 0.05) but not HC at 0.72 ± 0.14 (P=0.08); respectively. There was not a significant difference RA by IBD disease history. Increased intestinal permeability and increased TNF-α levels correlated with an increased rest activity fragmentation (IV) at R=0.35, P < 0.05 and R=0.37, P<0.05, respectively; and decreased rest-activity amplitude (RA) was associated with increased stool calprotectin at R=0.40, P<0,05. Analysis of intestinal microbiota showed a significant decrease in commensal butyrate producing taxa and increased pro-inflammatory bacteria with disrupted rest-activity cycles. Conclusion: In this study, different components of circadian misalignment by rest-activity cycles were associated with a more aggressive IBD disease history, increased intestinal permeability, stool calprotectin, increased pro-inflammatory cytokines, and dysbiosis. Wrist activity allows for an easy noninvasive assessment of circadian activity which may be an important biomarker of inflammation in IB